Latina Community College Presidents: Drawing from Cultural Intuition to Disrupt Leadership Norms in Higher Education - Cynthia Estrada; Eric R. Felix; Erin Nicole Reyes Vedar; Elizabeth Jimenez Perez (Education Sciences)
This study documents the unique personal and professional experiences that Latina leaders bring to the role of community college president. Guided by a Chicana Feminist conceptual framework, we examined the tools, strategies, and assets that Latina presidents possess to persist as higher education leaders within a white patriarchal dominant culture. As a research collective, we conducted platicas as a Chicana Feminist methodology with five Latina community college presidents in California. Each platica lasted between 60 and 90 min. Findings exemplified four sources of cultural intuition that Latina community college presidents drew from to redefine higher education leadership and drive student equity on campus: (1) personal experiences with marginality in educational spaces, (2) accumulated professional knowledge, (3) scholarly training in graduate school, and (4) the process of leading itself. The study found that Latina presidents possessed important knowledge and distinct perspectives based on their experiences as Women of Color, children of immigrants, and former community college students to guide their leadership approaches in equity driven ways.